+0  
 
+3
538
10
avatar+1760 

$$Let the term $S_n$ be the sum of the first $n$ powers of $2$. For instance, $S_3 = 2^0 + 2^1 + 2^2 = 7$. Find the largest possible value of the greatest common divisor of two consecutive terms, $S_n$ and $S_{n+1}$, for any $n$.$$ Let the term $S_n$ be the sum of the first $n$ powers of $2$. For instance, $S_3 = 2^0 + 2^1 + 2^2 = 7$. Find the largest possible value of the greatest common divisor of two consecutive terms, $S_n$ and $S_{n+1}$, for any $n$.

Mellie  Jun 23, 2015

Best Answer 

 #5
avatar+91051 
+13

Hi again anon, why don't you join up and take on an individual identity ?  :)

Anyway,  we have

 

 

$$\\S_n=2^n-1\\\\
S_{n-1}=2^{n-1}-1=2*2^n-1$$

 

So we want the greatest common divisor between these two terms.

It is obvious that for many values of n this will be 1 but do not know how to show that this is always the case.

Melody  Jun 25, 2015
Sort: 

10+0 Answers

 #1
avatar
+13

I give this a try(pls someone check this afeter I done)

Let the term $S_n$ be the sum of the first $n$ powers of $2$. For instance, $S_3 = 2^0 + 2^1 + 2^2 = 7$. Find the largest possible value of the greatest common divisor of two consecutive terms, $S_n$ and $S_{n+1}$, for any $n$.

Sn=2^0+2^1+2^2+.......2^(n-1)

consider the pattern 

2^0=(2^1-1)/2-1

2^0+2^1=(2^2-1)/(2-1)

2^0+2^1+2^2=(2^3-1)/(2-1)

2^0+2^1+2^2+2^3=(2^4-1)/(2-1)

.....

2^0+2^1+2^2+2^3.......+2^(n-2)+2^(n-1)=(2^n-1)/(2-1)

2^0+2^1+2^2+2^3.......+2^(n-2)+2^(n-1)+2^n=[2^(n+1)-1]/(2-1)

S{n}=2^0+2^1+2^2+2^3.......+2^(n-2)+2^(n-1)=(2^n-1)/(2-1)

S{N+1}=2^0+2^1+2^2+2^3.......+2^(n-2)+2^(n-1)+2^n=[2^(n+1)-1]/(2-1)

so the greatest common divisor would be 2-1=1

Guest Jun 25, 2015
 #2
avatar+91051 
+8

Hi anon, thanks for that answer   

I have NOT checked you logic, I have only coded it so it is more easily read 

Perhaps you shoulod just check that what i have written is what you intended :)

--------------------------------------------------------------------------------------------

 

I give this a try(pls someone check this afeter I done)

Let the term $$S_n$$ be the sum of the first $n$ powers of $2$. For instance,   $$S_3 = 2^0 + 2^1 + 2^2 = 7$$

Find the largest possible value of the greatest common divisor of two consecutive terms, $S_n$ and $S_{n+1}$, for any $n$.

 

 

$$\\Sn=2^0+2^1+2^2+.......2^{n-1}\\\\
$consider the pattern$ \\\\
2^0=\frac{(2^1-1)}{2-1}\\\\
2^0+2^1=\frac{(2^2-1)}{(2-1)}\\\\
2^0+2^1+2^2=\frac{(2^3-1)}{(2-1)}\\\\
2^0+2^1+2^2+2^3=\frac{(2^4-1)}{(2-1)}\\\\\\
2^0+2^1+2^2+2^3.......+2^{n-2}+2^{n-1}=\frac{(2^n-1)}{(2-1)}\\\\
2^0+2^1+2^2+2^3.......+2^{n-2}+2^{n-1}+2^n=\frac{2^{n-1}-1}{(2-1)}\\\\
S{n}=2^0+2^1+2^2+2^3.......+2^{n-2}+2^{n-1}=2^{n}-1\\\\
S{n+1}=2^0+2^1+2^2+2^3.......+2^{n-2}+2^{n-1}+2^n=2^{n+1}-1\\\\
$so the greatest common divisor would be $2-1=1\\\\$$

Melody  Jun 25, 2015
 #3
avatar
+10

...Thank you Melody.

I dont really know my anwser whther is right or not.I had ever taught by myself how to do this kind of question before.So,I dont really know.

....I found a mistake,the question said ,"for any $n$."when n=-1,S{n}=?

Guest Jun 25, 2015
 #4
avatar+91051 
+13

Hi anon,

n has to be greater than or equal to 1 - that is just assumed :)

Melody  Jun 25, 2015
 #5
avatar+91051 
+13
Best Answer

Hi again anon, why don't you join up and take on an individual identity ?  :)

Anyway,  we have

 

 

$$\\S_n=2^n-1\\\\
S_{n-1}=2^{n-1}-1=2*2^n-1$$

 

So we want the greatest common divisor between these two terms.

It is obvious that for many values of n this will be 1 but do not know how to show that this is always the case.

Melody  Jun 25, 2015
 #6
avatar+889 
+10

It's a geometric series with first term 1 and common ratio 2, so

$$S_{n}=2^{n-1}-1,$$

and

$$S_{n+1}=2^{n}-1.$$

Suppose that both of these are exactly divisible by some integer k (say), then there will be integers say s and t such that

$$s\times k = 2^{n-1}-1, \; \text{ and }\; t\times k = 2^{n}-1.$$

Multiply the first of these equations by 2 and subtract that from the second one and you have

$$(t\times k)-(2\times s\times k) = 1,$$

or,

$$k(t-2s)=1.$$

Since k, t and s are integers, it follows that

$$k = 1 \; (\text{and }\; t - 2s=1).$$

Bertie  Jun 25, 2015
 #7
avatar+91051 
+5

Thanks Bertie, that is really neat.  It is so easy when YOU do it.   

 

s,k and t must all be positive integers I think.   :/

Melody  Jun 25, 2015
 #8
avatar+889 
+10

Nit-picker !

But you're correct, I was careless, I should have stated that k was positive.

Bertie  Jun 25, 2015
 #9
avatar+78754 
+10

Notice that the sum of the first n terms and the next term to be added are relatively prime, since their difference is just 1.  For instance:    1  + 2  + 4  = 7.  And the next term to be added is 8.

 

But, if A, B are relatively prime, then their sum, A + B, (the next  term in the series), must be relatively prime to B, because their difference is just A. [If A and B weren't relatively prime, there would be some factor, k, that would divide them both and would also divide their sum.]

 

Thus, each successive term in the series is relatively prime to its successor........

 

 

CPhill  Jun 25, 2015
 #10
avatar+91051 
+5

Sorry Chris but that is not obvious to me :(

 

I do understand your's Bertie, and I just could just not resist nit-picking.

It is a very rare oportunity for me to be able to pick you up one anything and I just had to make the most of it!  

 

Besides, mathematicians are nit-pickers, it is a part of our trade :))

 

Thank you both for answering.  For a while I did not think anyone was going to   :)

Melody  Jun 26, 2015

6 Online Users

avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details